Thioimidazoline based compounds reverse glucocorticoid resistance in human acute lymphoblastic leukemia xenografts1. Issue 22 (14th June 2015) - Toscan, Cara E.; Rahimi, Marwa; Bhadbhade, Mohan; Pickford, Russell; McAlpine, Shelli R.; Lock, Richard B.
<x xml:space="preserve">Abstract</x> Glucocorticoids form a critical component of chemotherapy regimens for pediatric acute lymphoblastic leukemia and initial poor response to glucocorticoid therapy is predictive of inferior outcome.